THU0318 The Pregnancy Experience of 85 Women with SLE Followed in A Specialist Lupus Clinic Compared To The General Population. (15th July 2016) - Murphy, C.-L.M.; Croca, S.; Rahman, A.; Giles, I.
Abstract : Background: SLE affects women of childbearing age. Research suggests that patients with SLE have similar rates of pregnancy as other women but a higher rate of pregnancy loss [1]. Parity may be reduced due to infertility eg. secondary to antiphospholipid syndrome, pregnancy loss or personal choice. Concerns over teratogenic medication, disability and child health have been cited as personal reasons [2]. Objectives: Our aim was to carry out a retrospective analysis of the pregnancy experience of women with SLE followed up for a mean of 18 years in a specialist clinic. Methods: Pregnancy data were collected on 85 women with SLE via questionnaire between June and December 2015. Questions focused on parity, number of pregnancies, miscarriages, stillbirths, termination of pregnancy and number of live births. Questions related to pregnancy complications included pre-eclampsia, intrauterine growth retardation (IUGR), abruption placenta, gestational diabetes, caesarean sections (CS) and preterm labour <37 weeks. Data on smoking and serology were obtained from the medical records. Results: Of 85 women with SLE, the mean age was 45 years and mean follow-up was 18±11 years. Ethnicity was 53% white, 10.5% Asian, 27% Afro-Caribbean and 9% other. 20% were current/previous smokers. 43.5% were anti-Ro positive. 14% were LA positive, 15% were aCL positive and 8% were anti-β2GPI positive. The questionnaire results are summarised in Table 1, with comparison to UK population figures where they are available. Among the 45 parous women, there were 83 live births. 80% (36/45) had 1–2 children. 15% had 3 (7/45) children and 4% (2/45) had 4 children. No patient had more than 4 children. Miscarriages occurred in 22% (19/85); 18% (8/45) had preterm labour, 4.4% (2/45) had hypertension during pregnancy, 9% (4/45) had CS, 4.4% had low birth weight. Other adverse pregnancy outcomes included placental abruption (2.2%), ectopic pregnancy (2.2%), IUGR (2.2%) and stillbirth (twins) (2.2%). Conclusions: The major finding of this study was that almost half the respondents had no children, more than double what one would expect in UK women of the same mean age. This was primarily due to never having been pregnant rather than increased rate of TOP or miscarriage. Further research into the social and/or medical reasons for this avoidance of pregnancy is required. Pregnancy morbidity amongst those who had been pregnant was common especially miscarriage and pre-term labour. References: Petri, M. and J. Allbritton, Fetal outcome of lupus pregnancy: a retrospective case-control study of the Hopkins Lupus Cohort. J Rheumatol, 1993. 20(4): p. 650–6. Clowse, M.E., et al., Effects of infertility, pregnancy loss, and patient concerns on family size of women with rheumatoid arthritis and systemic lupus erythematosus. Arthritis Care Res (Hoboken), 2012. 64(5): p. 668–74. Disclosure of Interest: None declared